1994
DOI: 10.1002/tox.2530090109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of the specificity of the brine shrimp and microtox assays to hepatotoxic (microcystin‐LR‐containing) cyanobacteria

Abstract: Specific, straightforward, and rapid procedures are required for the detection, identification, and quantification of the potent low molecular weight toxins that are produced by blooms and scums of cyanobacteria (blue-green algae) in waterbodies.Use of the Microtox bioluminescence assay and the brine shrimp (Artemia salina) has been advocated for the initial screening of cyanobacterial blooms for microcystin hepatotoxins. Inhibition of bacterial luminescence in the Microtox assay and brine shrimp mortality wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 28 publications
1
46
0
2
Order By: Relevance
“…The toxicity of the particles was assessed by means of the Artemia salina bioassay (Campbell et al, 1994;Metcalf et al, 2002). This bioassay was undertaken on nauplii of A. salina, obtained after exposing commercial Artemia cysts (Marinemix, Wimex.…”
Section: Toxicity Assessmentmentioning
confidence: 99%
“…The toxicity of the particles was assessed by means of the Artemia salina bioassay (Campbell et al, 1994;Metcalf et al, 2002). This bioassay was undertaken on nauplii of A. salina, obtained after exposing commercial Artemia cysts (Marinemix, Wimex.…”
Section: Toxicity Assessmentmentioning
confidence: 99%
“…For example, it has been used for the assessment of toxicity in remediated soil from a contaminated site with various pesticides and their major metabolites (19). The Microtox system has also been used to evaluate the effectiveness of toxicity reduction during wastewater treatment (63) and for initial screening of cyanobacteria blooms (7). Other potential uses of this system are within the Offshore Oil and Gas Industry to monitor discharges from offshore installations at source (62).…”
Section: The Microtox Systemmentioning
confidence: 99%
“…Although the assay is rather inadequate regarding the elucidation of the mechanisms of action, it is very useful to assess the potential toxicity of strains. It was found that artemia nauplii mortality correlated well with concentrations of cyanobacterial toxins namely hepatotoxins ( Campbell et al, 1994) and neurotoxins ( Kiviranta et al, 1991). Regarding rotifers, the genus Brachionus has a cosmopolitan distribution and the species B. plicatillis is particularly common in brackish and marine environments.…”
Section: Introductionmentioning
confidence: 99%